(3CKQ GdXQha GdESJKfGFjI Ydi eHOC GdTQYjI (B:s (3OQGSI ebGQfI (B/s - (3eLOj GdeJhdj GdSjO jhSa s; (3SdjeGf GdWMGhjs ((3GdbGgQI (B: s (3eLOj GdeJhdj GdSjO , s, 1990)
(3jOhQ gPG GdHMK Mhd GKQ GdXQha GdGSJKfGFjI Ydi eHOC GdTQjYI hGfg GUHM ef GdGgejg JfGhd eHOG GdTQjYg HTF ef GdJaUjd GdPi jJfGSH eY fWGb GdHMK heVehfg(B. (3hdPdc abO MQU GdcGJH Ydi JNUjU aUd JegjOi dJfGhd Pdc GdeHOC ef MjK GdebUhO Hg heUGOQg(B. (3hGNJJe gPG GdaUd HCjVGM eLed GdTQYjI hHUaI NGUI ef MjK hVYjJg Hjf bje GdKHGJ hGdJZjQ(B.s
(3GWQhMI OcJhQGIs
(3JTJed Ydi EQLGYGJ HHdjhLQGajI s
Keywords: (3GdXQha GdGSJKfGFjIs; (3GdWhGQF s; (3eHOC GdTQYjIs; (3GdQbGHI GdbVGFjI s